A piezoelectric energy harvester for rotating environment using a linked E-shape multi-beam. (February 2019) - Ramírez, J.M.; Gatti, C.D.; Machado, S.P.; Febbo, M.
Abstract: This paper analyzes the effects of rotational motion on the performance of an innovative piezoelectric energy harvester (PEH) operating in a very low rotation speed (0.5 to 3 Hz) environment. The rotational energy harvester (REH) consists of two E-shape multiple beams system joined with a rigid beam. The harvester has masses attached and a MFC (Macro Fiber Composite) 2814 P2 piezoelectric sheet mounted on one of the multiple beams. The REH is mounted on a rigid plate that rotates at constant angular speed and has the possibility to adjust the hub distance with respect to the axis of rotation. One of the key points of the design is to have very low natural frequencies and the lowest possible physical volume. For the evaluation of the electro-mechanical response, a nonlinear one-dimensional finite element formulation is used. The proposed numerical approach is validated through Abaqus commercial software models and experimental tests. The performance assessment is done investigating the influence of the hub distance, the rotation speed, the centrifugal force, the softening effect and the electrical resistance over the output voltage and the power generation. Regarding harvester performance, promising results are obtained since the maximum output electric power is 200 μ W in a very low frequency interval at R = +0.03 m, for a physical volume of 140 cm 3 . In this sense, our proposal provides a prototype to power wireless autonomous monitoring systems of wind turbines of 30 kW.